Distribution and long-term change of the sea surface carbonate system in the Mozambique Channel (1963–2019). (May 2021) - Lo Monaco, Claire; Metzl, Nicolas; Fin, Jonathan; Mignon, Claude; Cuet, Pascale; Douville, Eric; Gehlen, Marion; Chau, Thi Tuyet Trang; Tribollet, Aline
Abstract: We report new oceanic carbonate system observations obtained during two cruises conducted in January 2004 (OISO-11) and April 2019 (CLIM-EPARSES) in the Mozambique Channel and estimate the long-term trend of sea surface fugacity of CO2 (fCO2 ) and pH using historical data. While in January 2004 the region was a large CO2 source, the ocean was near equilibrium in April 2019. Although this region experienced a dramatic cyclone event "Idai" in March 2019 leading to low salinity and low dissolved inorganic carbon (CT ) and total alkalinity (AT ) concentrations in the central channel, salinity normalized AT were unchanged and CT concentrations were higher in 2019 compared to 2004 by about 12 μmol.kg -1, likely due to anthropogenic CO2 uptake over 15 years. Compared to fCO2 observations of 1963 in the channel, the oceanic fCO2 was higher in 2004/2019 by about 100 μatm, an increase close to that observed in the atmosphere (90 ppm). A part of the fCO2 increase from 1963 to 2019 (about +10 μatm) is due to the long-term ocean warming in this region (+0.011 °C.decade -1 ). We estimated a mean decrease of −0.087 (±0.007) pH unit between 1963 and 2019, typical of the preindustrial versus modern change in the global ocean. Using other observations in the southern part of the Mozambique Channel (around 25°S) we estimated a pH trend of −0.0129.decade -1 (±0.0042) for 1963–1995 and −0.0227.decade -1 (±0.0048) for 1995–2019 suggesting a strengthening of acidification trend in the Mozambique Channel in agreement with the anthropogenic CO2 forcing. For the recent period, these rates were confirmed by reconstructed fCO2 and pH monthly fields using a neural network model. We noted however that the pH trend in the Mozambique Channel appeared lower than previous estimates at the scale of the Indian Ocean. Based on historical atmospheric CO2 data we estimated that pH in the Mozambique Channel was about 8.18 (±0.014) in the year 1800, i.e. 0.13 higher than in 2019. The concentration of CT in the year 1800 was likely around 1915 (±10) μmol.kg -1 . These results will contribute to a better understanding of the impacts of ocean acidification on coral reefs since the industrial revolution by (1) providing a reference level for the reconstruction of pH from coral core samples that were collected at different locations in this region in 2019 and (2) by informing environmental authorities aiming at preserving and protecting those threatened ecosystems. Highlights: New observations of the marine carbonate system in the Mozambique Channel. First evaluation of long-term trends of sea surface fCO2 and pH in the Mozambique Channel. The fCO2 increase and pH decrease are mainly attributed to anthropogenic CO2 uptake. Results suggest a strengthening of acidification trend in the Mozambique Channel since the mid-90s.